High temperature LTCC package for SiC-based gas sensor - Nowak, Damian; Kulczak, Dariusz; Januszkiewicz, Maksymilian; Dziedzic, Andrzej (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
A rapid progress in the development of semiconductor microelectronics is still observed. Miniaturization process of electronic devices is closely connected to packaging issues. In many cases package is as important as the device itself. Low temperature co-fired ceramics (LTCC) and thick-film technologies have the potential of incorporating multilayer structures and permit fabrication of special packaging systems. LTCC technology allows us to connect simply electrical or optical signals and to integrate passive components, heaters, sensors, converters, etc. In this paper, an LTCC package for SiC-based hydrogen gas sensor is presented. Some simulations of thermal properties were carried out and package structures were made and investigated. The package protects the sensor against mechanical damage and makes an easy connection of electrical signals possible. Moreover, the heater and temperature sensors allow proper temperature of an element to be obtained. Basic electrical parameters of an integrated heater as well as measured temperature distribution are presented.
Optica Applicata, Vol. 39, 2009, nr 4, s. 701-704
Keywords: optyka; thick-film; low temperature co-fired ceramics (LTCC); packaging